Opioid Use and Chronic Infections: The Value of Addressing the Syndemic in Correctional Settings Via Telemedicine Guidance and Broader Use of Long-Acting Medications. (2nd September 2020) - Krsak, Martin; Montague, Brian T; Trowbridge, Paul; Johnson, Steven C; Binswanger, Ingrid A
Abstract: In the United States, we are experiencing linked epidemics (a syndemic) of substance use disorders (SUDs) and infections associated with drug use, including unsafe injecting and unsafe sex in exchange for drugs or money. Current drug laws, together with risk-taking behavior among persons with SUDs, contribute to disproportionately high prevalences of these conditions in correctional settings. Detection and treatment of diseases with a high impact on public health are best addressed in the settings where such conditions are most prevalent (ie, jails and prisons for SUDs and chronic infections). The effectiveness, safety, cost of care. and public health impact of these conditions can be improved by means of broader screening and expanded access to specialty consultations through telemedicine/telehealth, along with broader use of long-acting medications for the treatment of human immunodeficiency virus and SUDs. Expanding telemedicine/telehealth, first for specialties which do not require advanced technology (eg, infectious diseases, addictions), can eventually lead to further advancements in correctional healthcare.